Adiabatic Shear Localization : Frontiers and Advances. - Dodd, Bradley (Elsevier insights., 2012)
Adiabatic shear localization is a mode of failure that occurs in dynamic loading. It is characterized by thermal softening occurring over a very narrow region of a material and is usually a precursor to ductile fracture and catastrophic failure. This reference source is the revised and updated version of the first detailed study of the mechanics and modes of adiabatic shear localization in solids. Building on the success of the first edition, the book provides a systematic description of a number of aspects of adiabatic shear banding. The concepts and techniques described in this work can usef.